Da simulação da morte: versão e aversão em Montaigne - Lucio Vaz de Oliveira (2007)
The work aims to investigate the actions and argumentative strategies proposed by Montaigne, in the Essays, in order to eliminate the fear of death. After a conceptual delimitation of the problem and a discussion on the question of immortality in the book, I undertake a study on the evaluation of the imagination faculty. Then, I inquire about the applicability of the imagination specifically to the problem of death and dying. So, I describe two diametrically opposed strategies that were defended by the author at different moments of his writing the Essays: in the first one, there is a positive evaluation of the method of constant mental simulation of death and, in the second one, Montaigne disbelieves the simulation of it and defends a confidence in the natural predisposition not to fear death and dying. Afterwards, I try to investigate the passage from the first strategy and attitude toward death to the second one. Once made these assessments almost exclusively focused on the Montaignes text confronted with some scholars readings, I go to historical observations on possible influences on Montaignes thought regarding the subject. At last, I try to show some tensions of the Montaignian teaching about death, among them that between the affirmation of its universality, prescribing the dissipation of its fear, and the recognition of an individual fear before the possibility of his own annihilation.